Political violence in Turkey, 1975-1980 the state at stake - Gourisse, Benjamin, 1980- (London)
viii, 224 sayfa
Keywords: “This book examines the period of political violence in Turkey between 12 March 1971 and 12 September 1980. It sets out a close analysis of the tactics used by the various protagonists in the conflict, showing how they took over public institutions, the first of which was the police. This book challenges the myth of a 'strong' Turkish state viewed as authoritative and autonomous from society, instead reflecting a state that was unable to contain the political mobilisation actually taking place. In the book, Benjamin Gourisse analyses the structure, mobilisation, and strategies of antagonistic radical political groups caught up in this dynamic of violence, including the far-left organisations and the Nationalist Movement, comprising the Nationalist Movement Party and its satellite organisations. Gourisse demonstrates that from 1975 to 1980, the state was never “out of play”. Quite the contrary, in fact, for its institutions, together with the practices, beliefs, and representations of their members and users, were central to the processes constituting the crisis.” --